Meeting Global Trends in Nigerian Architectural Education: A Case for The Green Building Concept - Ilesanmi, Oluropo Stephen; Ojo, Emmanuel Temitope; Kolade, Olaiya Olusegun; Folorunso, Sefunmi; Arawomo, Oladapo Augustine (Local Engineering, 2024)
The teaching of architecture as a course of study in a Nigerian Institutions dates back to the 1960s’. Although slight changes were being effected in the ensuing years, the curriculum on architectural education has largely remained the same. With the advent of globalization in more recent times however, architecture has been presented with new opportunities, challenges and trends. This paper identifies one of such contemporary issues as the green building concept. The concept, developed as a reaction to global outcry on the negative impact of buildings on the environment, imbibes eco-friendliness as its prime design philosophy. This paper however observes that although the green building concept currently attracts a tremendous amount of attention at the global level, the concept has not been commensurately reflected in the curriculum of architectural education in Nigeria. The paper therefore recommends a review of the curriculum to meet the new challenges and opportunities been presented by the green building concept. This it believes will keep architectural education in Nigeria abreast with an issue of current global interest and consequently enhance the global relevance of the Nigerian graduate architect.